Industrialización del Agave; Tzawarshampoo - Tuitise Tipán, José Raúl (2017)
The present research project was carried out in the canton Latacunga, parish Eloy Alfaro, Salache Bajo neighborhood, at the Technical University of Cotopaxi, Agroindustrial Engineering, in the agave research laboratory. Contributing with further investigation to the project of physical-chemical characterization of agave for agro-industrial purposes in the canton Latacunga; The main objective of the research project was to elaborate a natural shampoo based on saponins extracted from the rhizomes and leaves of the black agave (Agave americana), using the Soxhlet method using ethanol as solvent with the addition of two types of extracts one of Chamomile (chamaemelum nobile) and one of roses (pink), and two types of dyes an artificial and a natural; Which was obtained by maceration of ñachag roses. The methodology applied in the development of the research was: experimental, exploratory and descriptive research; Inductive, deductive and analytical methods; Observation and survey techniques. The presence of saponins was determined by the foam test resulting in treatment 5 (a2b1c1); (50% rhizome - 50% leaf, chamomile extract, artificial coloring); As well as pH and viscosity tests, resulting in the treatment. With the saponins extracted from both rhizomes and leaves of the agave, the shampoo was produced, which presented a good acceptability, this acceptance was determined by means of sensorial analysis verified with a survey carried out To the students of 8th cycle. A proximal analysis established by the Ecuadorian technical standard INEN 842 of tenso-active agents, shampoo requirements to make a comparison with the obtained results was also carried out.